Hungary : 2021 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2021)
Hungary's economy entered the COVID-19 pandemic on a strong footing and the authorities responded swiftly and strongly to the crisis it triggered. While the lockdowns weighed heavily on activity, the fast vaccination pace is allowing an early relaxation of containment measures, and the economy has started to rebound.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Hungary